Diabetic Nephropathy Is Accelerated by Farnesoid X Receptor Deficiency and Inhibited by Farnesoid X Receptor Activation in a Type 1 Diabetes Model - Wang, Xiaoxin X.; Jiang, Tao; Shen, Yan; Caldas, Yupanqui; Miyazaki-Anzai, Shinobu; Santamaria, Hannah; Urbanek, Cydney; Solis, Nathaniel; Scherzer, Pnina; Lewis, Linda; Gonzalez, Frank J.; Adorini, Luciano; et al. (Diabetes (New York, N.Y.), 2010)
The pathogenesis of diabetic nephropathy is complex and involves activation of multiple pathways leading to kidney damage. An important role for altered lipid metabolism via sterol regulatory element binding proteins (SREBPs) has been recently recognized in diabetic kidney disease. Our previous studies have shown that the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor, modulates renal SREBP-1 expression. The purpose of the present study was then to determine if FXR deficiency accelerates type 1 diabetic nephropathy in part by further stimulation of SREBPs and related pathways, and conversely, if a selective FXR agonist can prevent the development of type 1 diabetic nephropathy. Insulin deficiency and hyperglycemia were induced with streptozotocin (STZ) in C57BL/6 FXR KO mice. Progress of renal injury was compared with nephropathy-resistant wild-type C57BL/6 mice given STZ. DBA/2J mice with STZ-induced hyperglycemia were treated with the selective FXR agonist INT-747 for 12 weeks. To accelerate disease progression, all mice were placed on the Western diet after hyperglycemia development. The present study demonstrates accelerated renal injury in diabetic FXR KO mice. In contrast, treatment with the FXR agonist INT-747 improves renal injury by decreasing proteinuria, glomerulosclerosis, and tubulointerstitial fibrosis, and modulating renal lipid metabolism, macrophage infiltration, and renal expression of SREBPs, profibrotic growth factors, and oxidative stress enzymes in the diabetic DBA/2J strain. Our findings indicate a critical role for FXR in the development of diabetic nephropathy and show that FXR activation prevents nephropathy in type 1 diabetes.